COVID-19 pandemic and the use of tele-health by pediatricians and pediatric post graduate residents - Tehreem Fatima; Zaib Nasir; AbdulAhad Jamshaid; Hina Ayesha (Journal of University Medical & Dental College, 2022)
BACKGROUND & OBJECTIVE: During the COVID-19 pandemic, burden on healthcare facilities has increased worldwide; which has led to acceptance of the ‘telehealth services’ by the pediatricians. Objective of this study was to determine the impact on frequency of use of tele-health services by pediatricians during the COVID-19 pandemic; and to determine the factors promoting and preventing the use of tele-health services by pediatricians. METHODOLOGY: This descriptive cross-sectional study was carried out from August 2020 to January 2021 among the pediatricians of Children Hospital Faisalabad and other affiliated hospitals of Faisalabad Medical University, Pakistan. An e-questionnaire was circulated among 357 pediatricians, which was filled and submitted by 114 pediatricians online. Demographic details and other data were collected and analyzed by SPSS v.20. P-value <0.05 was taken as significant. RESULTS: Out of 114 participants, 29(25.4%) paediatricians were already using Telehealth before the COVID-19 pandemic. Whereas, 101(88.6%) participants used Telehealth during the pandemic. There was an increase in frequency of telehealth use during the pandemic by 72(63.2%) paediatricians (p-value= 0.037). Most common factor promoting the use of telehealth during pandemic was ‘decreased chance of cross infection and maintenance of social distancing’. Most frequent factor preventing its use was ‘lack of confidence on virtual examination findings’. CONCLUSION: Telehealth provided an effective means of practicing social distancing by the paediatricians without any breach in healthcare provision. However, there are a few factors contributing to hesitancy towards it. Therefore, more platforms must be provided and incentives to be given to paediatricians to promote the use of telehealth.